A Microwave Photonics True-Time-Delay System Using Carrier Compensation Technique Based on Wavelength Division Multiplexing - Yiru Zhao; Chaoquan Wang; Zeping Zhao; Weijie Zhang; Jianguo Liu (Photonics, 2022)
A novel microwave photonic true-time-delay (TTD) system using carrier compensation technology is proposed and experimentally demonstrated. Wavelength division multiplexing combines ten lasers into a single beam. We separate one channel from the laser as a compensating carrier, and the compensation carrier is combined with the time-delayed optical signals to be detected. Meanwhile, sideband signals are amplified effectively thanks to carrier-suppressed double-sideband (CS-DSB) modulation. Therefore, the power of both the central optical carriers and sidebands is guaranteed, which produces a better beat frequency result than the TTD system without carrier compensation. The simulation results confirm that the signal amplitude has an order of magnitude improvement due to the compensation. With employing the delay fibers based on multiple-fiber Bragg gratings (MFBGs), the experimental delay and response time reach 90.160 μs and 160.80 ns. The proposed technique can find applications in time-delay beamforming of phased array antennas (PAAs).